Integrative biochar and melatonin application mitigates lead toxicity in rice by modulating antioxidant activities and iron plaque formation and downregulating the expression of metal uptake genes - Khan, Tahir Abbas; Su, Qitao; Guoqin, Huang; Du, Zhixuan; Noor, Mehmood Ali; Asseri, Tahani A. Y.; Hassan, Muhammad Umair (Frontiers in Plant Science, 2025)
Lead (Pb) is a common toxic metal that causes severe health and environmental problems. However, the defensive role and underlying mechanism of combined biochar (BC) and melatonin (MT) against Pb stress are still unclear. Therefore, to fill this gap, this study investigated the impacts of BC and MT on rice growing in Pb-polluted soil. This study included different treatments: control, Pb stress (300 mg kg−1), Pb stress (300 mg kg−1) + BC (2%), Pb stress (300 mg kg−1) + MT (30 µM), and Pb stress (300 mg kg−1) + BC (2%) + MT (30 µM). Pb reduced rice growth and yield by hindering photosynthetic pigments, relative water contents (RWCs), osmolyte synthesis, nutrient uptake, increase in oxidative markers, and Pb accumulation. Biochar and MT increased rice productivity by increasing chlorophyll synthesis, osmolytes, and nutrient uptake and decreasing Pb accumulation. The co-application of BC and MT decreased Pb accumulation in the roots (30.40%) and shoots (72.79%), the translocation factor (30.01%), the biological accumulation coefficient (20.17%), and the soil Pb concentration (59.02%). The co-application of BC and MT enhanced proline (39.65%), soluble protein (47.09%), ascorbate peroxidase (APX; 26.47%), catalase (CAT; 65.51%), peroxidase (POD; 89.56%), and superoxide dismutase (SOD; 65.53%) activities, which ensured better productivity. Additionally, the BC+MT application increased the expression of antioxidant defense genes (OsAPX, OsCAT, OsPOX, and OsSOD) and decreased the expression of metal transporter genes (OsHMA9 and OsNRAMP5), which protected the rice plants from damage caused by Pb toxicity. These results suggested that BC+MT could be a promising strategy to mitigate Pb toxicity and maintain sustainable and safer food production.